L’eau urbaine ou le pouvoir de renaturer - Franck Scherrer (Cybergeo)
Many urban policies (urban renewal, waterfront renewal, environmental protection, leisure and cultural amenities development, public spaces development…) focus on the water in the city (river, Lake, sea…). These urban policies are in competition in order to re-nature the urban spaces. But this reference to re-naturation hide different systems of values and different coalitions which fight to win this power of re-naturing the city.